(untitled) (MAUSAM, 1980)
The, onset of monsoon has been studied with the help of north-south time cross sections along 75 deg. E at various levels in the atmosphere. The study of flow, changes of temperature and moisture along this section show important developments and features in Arabian Sea during the onset of monsoon. Finally, the advance of monsoon with the movement of depression off west coast has been associated.